In vitro Evaluation of Tinidazole Bioadhesive Vaginal Gels - Zainab T.Salih (College of Pharmacy University of Baghdad, 2017)
Many trials were made to prepare Tinidazole 2% as bioadhesive vaginal gels using different gel bases including hydroxypropyl methyl cellulose (3 and 4% w/w), methylcellulose (3 and 4%w/w) and    carboxymethylcellulose (2 and 3% w/w) .Swelling index of the polymers,pH , viscosity , bioadhesive force , and in-vitro drug release to the simulating vaginal fluid (S.V.F.) were investigated for all the prepared bioadhesive gels . The mechanism of drug release from the gel bases was also investigated. The results revealed that C MC 3% gave the highest viscosity and bioadhesive strength with the lowest release rate while lowest viscosity and bioadhesive force was obtained with HPMC gel base with the highest release rate. The mechanism of drug release was affected by the type of gel base. Fickian diffusion was obtained with all gel bases. Key words:  Tinidazole, bioadhesive polymers, gels